2021
DOI: 10.2991/assehr.k.211223.040
|View full text |Cite
|
Sign up to set email alerts
|

Developing Students’ English Skill Through Digital Video as Multimodal for Young Learners in Online Learning

Abstract: This study described EFL young learners how to develop their English using digital video as multimodal in online learning. Recently, all the processes of teaching-learning have been conducted in online learning mode. Therefore, technology has an important role to motivate students, especially young learners, to learn and improve their English skills. Using digital video can help learners to both interpreting and producing multimodal texts. It can also develop young learners for making meaning since they can wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…According to Bikowski & Casal (2018) in their study, the application of a customized interactive digital textbook elevates students' engagement during the learning process. Similarly, Susanti et al (2022) contend that the combination of some modes such as pictures and colors can assist students to learn. As a result, students" motivation increases as well as the improvement of their learning (Martínez Lirola, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bikowski & Casal (2018) in their study, the application of a customized interactive digital textbook elevates students' engagement during the learning process. Similarly, Susanti et al (2022) contend that the combination of some modes such as pictures and colors can assist students to learn. As a result, students" motivation increases as well as the improvement of their learning (Martínez Lirola, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Practically, the era of digital gives a massive contribution to the development of modality as a new method to learn a foreign language (Cowan & Kress, 2017;Ezeh, 2021) as well as the way to effectively engage student to learn (Ilmi et al, 2020). Moreover, the presence of digital environment simplifies the teachers to combine different modes ( (Adami, 2015) such as videos and audio (Susanti et al, 2022). Therefore, This technology offers new perspectives on how to use textbooks in learning.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a video combines two learning modes, visual and auditory, and these features trigger an enjoyable learning atmosphere (Rohana, 2017). On the visual side, the video offers various attractive images or animations for students to observe during the learning process (Susanti et al, 2022) and creates a non-boredom learning environment (Rahayu, 2020). It also facilitates the students to gain visual input on proper signs, gestures, or facial expressions, which can support the context of the utterances (Mellit & Djerrah, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Syafiq , : ‫البحث‬ ‫‪The‬عنوان‬ Effectiveness of a Program Based on Digital Posters and Video-Based Reflection in Developing EFL Fluency Skills among Preparatory Stage Pupils(2021) reported enhanced English-speaking skills when using YouTube videos in the classroom. Eissa(2021) demonstrated that online video tours in popular tourist destinations significantly improved the speaking skills of Egyptian secondary school students Susanti, Presdyasmara, Dewi, & Wardani (2021). showed that young EFL learners could enhance their English proficiency through multimodal online learning using digital video.Mahdi (2022) highlighted the positive impact of multimedia use in the classroom on Arabic-speaking undergraduate English students' development of EFL speaking and presentation skills Muslem (2022).…”
mentioning
confidence: 99%